Analysis Of Zakat Utilization Patterns To Improve The Economy Of Zakat Recipient Families - Uncu, Adeliza Eva; Kosasih, Aceng; Sari, Indah (Jurnal I-Philanthropy, 2025)
This research aims to analyze the patterns of zakat fund utilization by recipients (mustahik) and identify factors influencing these utilization patterns. Using a qualitative approach with in-depth interviews of 20 zakat recipients, this study reveals that the majority of zakat funds are utilized to fulfill daily basic needs such as food supplies. In addition, the study found allocations of zakat funds for children's education, small business capital, and healthcare needs. Factors influencing utilization patterns include the urgency of family needs, demographic characteristics, recipients' experience and skills, and the amount of zakat received. This research concludes that although consumptive utilization remains dominant, there is a positive trend where some recipients are beginning to allocate zakat funds for long-term investments such as education and productive enterprises, which potentially provide more sustainable impact on poverty alleviation and welfare improvement.